Translation of “and” by students of Mandarin Language Diploma : a translation evaluation - Henggar Prasetyowati; Adilla Achmad Syahputri; Zuyinatul Isro; Chendy Arieshanty (University of Muhammadiyah Purwokerto, 2022)
This study examined the technique and quality of the translation of the conjunctions “and” done by students in socio-cultural subjects. The researchers conducted observations on the translation of students of the Universitas Jenderal Soedirman (Unsoed) Chinese Language Diploma Program (D3) who enrolled in the socio-cultural translation course. The results of their translation were then analyzed in the sense of their techniques used and the quality of their translation. Moreover, questionnaires were distributed to get suggestions for improvements to the teaching system, especially translation. The results showed that the error was dominated by the ambiguity of meaning caused by the incorrect choice of conjunctions, while the technique used was not entirely correct. This happens due to the lack of student competence, especially in mastering words and contexts of the conjunctions used.